Analysis of 33 pediatric trauma victims in the 1999 Marmara, Turkey earthquake - ALPAY, HARİKA (W B SAUNDERS CO, 2001)
Background/Purpose: The Marmara earthquake, which destroyed more than 150,000 buildings and caused 15,000 deaths and 40,000 casualties, resembled the Hanshin-Awaji earthquake in many respects. Previous reports from similar disasters from several centres have not addressed trauma in the pediatric age group. The aim of this study was to analyze the clinical and laboratory data of pediatric trauma patients referred to a tertiary center after the 1999 Marmara earthquake. Methods: The medical records of 33 injured children, aged from 14 days to 16 years, were reviewed retrospectively. The time spent buried under rubble, type of injury, treatment given, complications, laboratory data, and development of acute renal failure (ARF) were noted. Patients in whom ARF developed were treated with a standard regimen of fluid replacement, alkalinization, and diuretics. Limbs with crush injuries were managed as conservatively as possible. Results: All except 3 cases were evacuated from under the debris of collapsed buildings after 1 to 110 (mean, 30.04 +/- 6.48) hours. Seventy-eight percent were transported to our center within the first 3 days. Crush injury (CI) was present in 15 cases, and in 10 of them ARF had already developed by admission. Although serum levels of creatinine were elevated (1.2 to 5 mg/dL) in all cases with ARF, hyperkalemia was observed in only 4. The mean serum creatinine kinase (CK) level of cases with crush syndrome (CS) was 6,040 +/- 4,158 U/L. No significant correlations were detected between the development of CS, age, the time spent under the rubble, the time before admission, or the number of crushed extremities. Conclusions: CI and CS were the most common entities encountered among our pediatric patients after the 1999 Marmara earthquake. The high incidence of ARF indicates the importance of medical management of this age group during rescue. Because neither laboratory data nor clinical findings predicted CS in our patients, we recommend close observation and monitoring of children with CI for the development of ARF. Copyright (C) 2001 by W.B. Saunders Company.
Keywords: Crush syndrome; crush injury; acute renal failure; multiple trauma; earthquake disasters; HANSHIN-AWAJI-EARTHQUAKE; ACUTE-RENAL-FAILURE; CRUSH-SYNDROME; INJURY; RHABDOMYOLYSIS